In Loving Hands: How Founders’ Affective Commitment Strengthens the Effect of Organizational Flexibility on Firms’ Opportunity Exploitation and Performance - Pryor, Christopher; Li, Chang; Sergeeva, Anastasia V.; Pryor, Iana S. (Frontiers in Psychology, 2022)
Is flexibility or formality more useful for organizations that are pursuing improved performance? Organizational structure scholars offer opposing answers to this question, and empirical results have been mixed. Our study contributes to this research by describing a mediational model that links organizational flexibility to performance via opportunity exploitation. Specifically, we argue that flexible firms are able to exploit a greater number of opportunities, which, in turn, can improve performance. We also argue that the indirect effect of flexibility on performance via opportunity exploitation is stronger when top executives display higher affective commitment for their firms, meaning that they have a positive emotional attachment to their firms. Top executives with higher affective commitment can mitigate the downsides experienced by the staff of flexible firms, such as uncertainty and negative affect, which improves the outcomes of flexibility. Drawing on a sample of 211 firms and their founders, we find support for our hypotheses.